A Clay Figurine of Carbonized Material Temper - Suganuma, Wataru; Yoshida, Kunio; Miyauchi, Nobuo; Miyao, Toru (Nihon Kokogaku(Journal of the Japanese Archaeological Association), 2007)
We found some unknown black material in the temper of a clay figurine of Middle Jomon period that was excavated from Habakami site in Tokamachi city, Niigata prefecture. This paper focuses on the origin of the black material, and problems of containing the black material. The black material was examined by observation of soft X-ray images and X-ray computed tomography images, Xray fluorescence analysis, stable isotope analysis, and radiocarbon dating. The following results have been speculated: (1) Tempering materials in the clay figurine are mixed homogenously, and the black material was kneaded in the body paste of the clay figurine. (2) The black material is carbonized material, and those stable carbon and nitrogen isotope ratios show the range of values of Cplant species. (3) Radiocarbon age of the black material corresponds to the chronological date of these clay figurines' type. Therefore, it does not seem that the black material originated from natural sedimentary clay. It is thought that the black material kneaded in the raw body paste of the clay figurine is carbonized material. Examples of folk customs and ethnographical data provide supporting evidence for embodiment of clay figurines in not only physical form but also production processes from selection of raw materials to finishing were considered. Carbonized material in a clay figurine of Habakami site might be located in such a process.